Predictably irrational : the hidden forces that shape our decisions the hidden forces that shape our decisions - Ariely, Dan. (New York : Harper Perennial, 2010)
An evaluation of the sources of illogical decisions: explores the reasons why irrational thought often overcomes level-headed practices, offering insight into the structural patterns that cause people to make the same mistakes repeatedly.
Introduction -- How an injury led me to irrationality and to the research described here -- The truth about relativity: why everything is relative, even when it shouldn't be -- The fallacy of supply and demand: why the price of pearls, and everything else, is up in the air -- The cost of zero cost: why we often pay too much when we pay nothing -- The cost of social norms: why we are happy to do things, but not when we are paid to do them -- The influence of arousal: why hot is much hotter than we realize -- The problem of procrastination and self-control: why we can't make ourselves do what we want to do -- The high price of ownership: why we overvalue what we have -- Keeping doors open: why options distract us from our main objective -- The effect of expectations: why the mind gets what it expects -- The power of price: why a 50-cent aspirin can do what a penny aspirin can't -- The context of our character, part I: why we are dishonest, and what we can do about it -- The context of our character, part II: why dealing with cash makes us more honest -- Beer and free lunches : what is behavioral economics, and where are the free lunches?
The word "irrational" is displayed upside down on cover title and spine title.
Includes bibliographical references.
Keywords: Economics -- Psychological aspects; Decision making; Consumer behavior